Penerapan Sistem Informasi E-Posyandu dalam Pengawasan Pertumbuhan Gizi Anak di Posyandu Kelurahan Mojosongo Surakarta - Ahmad Fauzi; Budi Al Amin; Doddy Satrya Perbawa; Galih Setiawan Nurohim (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Integrated Service Posts (Posyandu) are important facilities for monitoring children's nutritional growth and development, but there are still many posyandu that use manual methods for recording data. This results in obstacles such as inaccurate data, delays in decision making, and difficulty in accessing information. To overcome this problem, the E-Posyandu information system was implemented at the Posyandu, Mojosongo Village, Surakarta. E-Posyandu is a digital platform designed to facilitate automatic and structured recording, storage and processing of children's nutritional data. This research aims to examine the effectiveness of implementing the E-Posyandu system in improving monitoring of children's growth and nutritional status in Mojosongo Village. By using this technology, the monitoring process becomes more efficient, data is easier to access, and the potential for recording errors can be minimized. Apart from that, this system also offers reminders and notification features to parents regarding the posyandu schedule and necessary health measures.The results of the implementation show an increase in the accuracy and speed of collecting child nutrition data, as well as increased parent participation in monitoring their child's health. It is hoped that E-Posyandu can become an innovative model to be applied in other posyandu in Indonesia.